Assessing and mitigating the economic effects of the corona virus disease (COVID-19) pandemic in the West African Monetary Zone - Ngozi Eunice Egbuna; Maimuna John-Sowe; Santigie M. Kargbo; Dauda Mohammed; Hissan Abubakari; Kormay Adams; Eric Sambolah (West African Journal of Monetary and Economic Integration, 2020)
This paper explores the macroeconomic implications of the COVID-19 pandemic in the WAMZ and discusses measures that could be employed to mitigate the adverse economic effects of the pandemic to preserve the gains already achieved towards regional integration. It identifies the channels through which the various containment measures pursued globally and by WAMZ countries to mitigate the spread of the virus slow economic growth in WAMZ countries, including weakening of fiscal positions; reducing tourism, trade, remittances flows and foreign direct investment, and disruptions to local production. The policy responses proffered to Member States were validated by engaging Central Banks and Ministries of Finance, which allowed us to develop policy priorities that would complement the efforts of Member States to mitigate the adverse economic effects of the pandemic in these countries. This paper proffers measures to cushion the short-to medium-term dampening effects of the pandemic, including the deferment of tax obligations; extending credit facilities to targeted small and medium enterprises (SMEs); temporary extensions of loan maturities of businesses exposed to sectors mostly affected by the COVID-19 containment measures; strengthening cross-border trade and financial linkages; and supporting domestic production, particularly in the agricultural sector. It further recommends that WAMZ countries develop a framework for diversifying their economies, as a long-term strategy to support strong and sustainable growth, promote similarity in economic structures to foster regional integration and build economic resilience in the long run. This should be complemented by a regional health strategy to contain future health crises and mitigate potential adverse economic effects.
Keywords: E32; I15; N17; 330; Covid 19 pandemic; containment measures; economic growth; WAMZ